Engineering Tables and Data - Howatson, A. M. author. aut Link
VIII, 168 p.
Keywords: This book brings together information which is used by engineers, and needed especially by students of engineering, but difficult to find in a collected form. In this respect engineering, perhaps because it is more often divided into separate branches, has so far been less well served than the other physical sciences; we hope to have in part redressed the balance. The contents are designed chiefly for engineering students of all kinds in universities and colleges, but they should also prove useful to practising engineers as a general reference. There was some difficulty in choosing numerical values for parts of the section Properties of Matter. Information was culled from a range of sources which sometimes show an alarming lack of consistency. Given a choice, we have used values which are either average or more likely to be reliable. The degree of tolerance required varies very widely between, for example, the precision to which thermodynamic proper ties of steam are known and the uncertainty in those mechanical properties of solids which depend strongly on quality and preparation. The tables on pages 4-12 inclusive are reproduced from S.M.P. Advanced Tables by permission of Cambridge University Press. The tables on pages 35 and 36 are reproduced from Elementary Statistical Tables: lindley and Miller, h./ permission of Cambridge University Press. The tables on pages 37 and 38 are reproduced by permission of the Biometrika Trustees.